Time domain para hydrogen induced polarization - Ratajczyk, Tomasz; Gutmann, Torsten; Dillenberger, Sonja; Abdulhussaein, Safaa; Frydel, Jaroslaw; Breitzke, Hergen; Bommerich, Ute; Trantzschel, Thomas; Bernarding, Johannes; Magusin, Pieter C. M. M.; Buntkowsky, Gerd (Solid State Nuclear Magnetic Resonance)

Photoluminescence and optical gain of Ga(NAsP) heterostructures pseudomorphically grown on silicon (001) substrate - Koukourakis, Nektarios; Funke, Dominic; Gerhardt, Nils Christopher; Hofmann, Martin R.; Klimasch, Max; Liebich, Sven; Zimprich, Martin; Kunert, Bernardette; Volz, Kerstin; Stolz, Wolfgang; Kubby, Joel; Reed, Graham T. (Silicon photonics VII)

Room temperature spin relaxation in quantum dot based spin-optoelectronic devices - Höpfner, Henning; Li, Mingyuan; Ludwig, Arne; Ludwig, Astrid; Reuter, Dirk; Wieck, Andreas; Gerhardt, Nils Christopher; Hofmann, Martin; Stromberg, Frank; Wende, Heiko; Keune, Werner (Ultrafast phenomena and nanophotonics XVI)

Inklusion in der Frühpädagogik: Episoden aus Krippe und Kindergarten - Albers, Timm (Karlsruher Pädagogische Beiträge. Zeitschrift für Erziehungswissenschaft und Fachdidaktik)

Time-resolved photoluminescence and optical gain in Ga(NAsP) pseudomorphically grown on silicon - Koukourakis, Nektarios; Gerhardt, Nils Christopher; Hofmann, Martin R.; Klimasch, Max; Liebich, Sven; Trusheim, Daniel; Zimprich, Martin; Volz, Kerstin; Stolz, Wolfgang; Kunert, Bernadette (76th Jahrestagung der DPG (76th annual conference of the DPG) and DPG-Frühjahrstagung (spring meeting) of the Condensed Matter Section (SKM) with further DPG Divisions: Environmental Physics, Microprobes, Radiation and Medical Physics, as well as the DPG working groups: Energy, Equal Opportunities, Industry and Business, Information, Philosophy of Physics, Physics and Disarmament, young DPG)

Temperature dependence of the spin relaxation length in spin quantum dot LEDs - Höpfner, Henning; Ludwig, Arne; Ebbing, Astrid; Reuter, Dirk; Wieck, Andreas; Gerhardt, Nils Christopher; Hofmann, Martin R.; Stromberg, Frank; Wende, Heiko; Keune, Werner; Fritsche, Carola (76th Jahrestagung der DPG (76th annual conference of the DPG) and DPG-Frühjahrstagung (spring meeting) of the Condensed Matter Section (SKM) with further DPG Divisions: Environmental Physics, Microprobes, Radiation and Medical Physics, as well as the DPG working groups: Energy, Equal Opportunities, Industry and Business, Information, Philosophy of Physics, Physics and Disarmament, young DPG)

System development for spectroscopic optical coherence tomography - Jaedicke, Volker; Agcaer, Semih; Gerhardt, Nils Christopher; Hofmann, Martin; Goebel, Sebastian; Wiethoff, Helge; Welp, Hubert (Biomedical engineering)

Spin-controlled vertical-cavity surface-emitting lasers - Gerhardt, Nils Christopher; Hofmann, Martin (Advances in optical technologies)

Analysis of birefringence controlled ultrafast polarization oscillations in spin vertical-cavity surface-emitting lasers - Li, Mingyuan; Gerhardt, Nils Christopher; Hofmann, Martin; Ackemann, Thorsten (EOS annual meeting 2012 (EOSAM 2012))

integrative development of product and technology strategies - Brink, Volker; Gausemeier, Jürgen; Reymann, Felix (construction, issue 11/2012)

Who owns the customer? Disentangling customer loyalty in indirect distribution channels - Eggert, Andreas; Henseler, Jörg; Hollmann, Sabine (Journal of Supply Chain Management)

Strategic leadership with scenarios - Gausemeier, Jürgen; Grote, Anne-Christin (CONTROLLING - magazine for success-oriented corporate management)

Konzepte zur Regelung der Strahlungsleistung pulsbetriebener IR-Emitter - Hoof, Christian; Schlottmann, J.; Wetzlar, Dietmar; Henning, Bernd (16. GMA/ITG-Fachtagung. Sensoren und Messsysteme)
In optischen Messeinrichtungen (Abstandsmessung, NIR-Materialfeuchtemessung) werden häufig in einem schmalen Wellenlängenbereich strahlende, gepulste Infrarot-Emitter eingesetzt. Leistungsstarke Strahlungspulse sind notwendig, führen aber zu einer thermisch bedingten Abnahme der emittierten Strahlungsleistung und zu einer Verschiebung der Maximumwellenlänge. Die hierdurch entstehenden Messunsicherheiten werden aufgezeigt und Konzepte zu deren Verringerung dargestellt.

The production system of the future thinks and learns - Gausemeier, Jürgen; Iwanek, Peter; Köchling, Daniel (Industrieanzeiger)

Passability in education - a challenge for the future - Keil, Reinhard; Metternich, Hans-Jürgen; Ritzenhoff, Steffan

Summary and Outlook - Keil, Reinhard; Metternich, Hans-Jürgen; Ritzenhoff, Steffan

Thinking ahead of the future of additive manufacturing - scenario-based comparison of technology push and market pull - Gausemeier, Jürgen; Echterhoff, Niklas; Wall, Marina

Market and environmental scenarios in medical electronics - requirements for the products and services of tomorrow - Gausemeier, Jürgen; Lehner, Markus

Spin relaxation dynamics in spin-LEDs - Höpfner, Henning; Ludwig, Arne; Reuter, Dirk; Wieck, Andreas; Gerhardt, Nils Christopher; Hofmann, Martin R.; Fritsche, Carola; Stromberg, Frank; Wende, Heiko; Keune, Werner (76th Jahrestagung der DPG (76th annual conference of the DPG) and DPG-Frühjahrstagung (spring meeting) of the Condensed Matter Section (SKM) with further DPG Divisions: Environmental Physics, Microprobes, Radiation and Medical Physics, as well as the DPG working groups: Energy, Equal Opportunities, Industry and Business, Information, Philosophy of Physics, Physics and Disarmament, young DPG)

Erratum: “Room temperature spin relaxation length in spin light-emitting diodes” - [Appl. Phys. Lett. 99, 051102 (2011)] - Soldat, Henning; Li, Mingyuan; Gerhardt, Nils Christopher; Hofmann, Martin; Ludwig, Arne; Ebbing, Astrid; Reuter, Dirk; Wieck, Andreas; Stromberg, Frank; Keune, Werner; Wende, Heiko (Applied physics letters)